2009
DOI: 10.4049/jimmunol.0804277
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reporter Mouse Reveals Constitutive and Inflammatory Expression of IFN-β In Vivo

Abstract: Type I IFN is a major player in innate and adaptive immune responses. Besides, it is involved in organogenesis and tumor development. Generally, IFN responses are amplified by an autocrine loop with IFN-β as the priming cytokine. However, due to the lack of sensitive detection systems, where and how type I IFN is produced in vivo is still poorly understood. In this study, we describe a luciferase reporter mouse, which allows tracking of IFN-β gene induction in vivo. Using this reporter mouse, we reveal strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
250
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 208 publications
(268 citation statements)
references
References 35 publications
9
250
1
3
Order By: Relevance
“…To monitor induction of IFN-β in more detail, we also used mast cells and macrophages matured from bone marrows of the Δβ-luc mice (23). Consistently, L. monocytogenes and S. typhimurium elicited IFN-β responses in macrophages but not in mast cells (Fig.…”
Section: Ifn-β Impairs Mast Cell-dependent Mobilization Of Neutrophilmentioning
confidence: 99%
See 1 more Smart Citation
“…To monitor induction of IFN-β in more detail, we also used mast cells and macrophages matured from bone marrows of the Δβ-luc mice (23). Consistently, L. monocytogenes and S. typhimurium elicited IFN-β responses in macrophages but not in mast cells (Fig.…”
Section: Ifn-β Impairs Mast Cell-dependent Mobilization Of Neutrophilmentioning
confidence: 99%
“…To determine whether mast cells contribute to IFN-β response during bacterial infection in vivo, we used the IFN-β-luciferase reporter mouse (Δβ-luc) (23). Following i.p.…”
Section: Ifn-β Impairs Mast Cell-dependent Mobilization Of Neutrophilmentioning
confidence: 99%
“…MEFs were prepared from 13-day-old embryos of transgenic C57BL/6 knock-in mice carrying firefly luciferase (FF-Luc) cDNA instead of the IFN-b gene under the control of the endogenous IFN-b promoter (Lienenklaus et al, 2009). Bone marrow-derived pDCs were prepared from IFN-b deficient C57BL/6 mice (IFN-b 2/2 ) (Erlandsson et al, 1998) by cultivating bone marrow cells for 8 days in medium supplemented with Flt3-L (100 ng ml…”
Section: Methodsmentioning
confidence: 99%
“…MEFs were isolated from reporter mice carrying the IFN-b gene replaced by the firefly luciferase (FF-Luc) cDNA, thus allowing quantitative detection of IFN-b promoter activation. The expression of luciferase in the lysates of these cells correlates with the induction of endogenous IFN-b (Lienenklaus et al, 2009). Infection of these cells with different doses of recombinant THOV showed a strong activation of the IFN-b promoter by THOVML2 (Fig.…”
Section: Type I Ifn Induction By Thov Is Blocked By Mlmentioning
confidence: 99%
“…Recently, a reporter mouse which expresses green fluorescent protein in place of IFN-␣6 was used to demonstrate that alveolar macrophages contribute to IFN synthesis in the lungs of Newcastle disease virus (NDV)-infected animals (8). To visualize IFN synthesis in various cell types of the brain during infection with La Crosse bunyavirus (3), we had employed a different reporter mouse in which the IFN-␤-coding region was replaced by firefly luciferase (9). These studies clearly showed that virus-encoded IFN-antagonistic factors may display their activities in particular cell types of infected organs but, at the same time, may fail to inhibit IFN synthesis by immune cells (3,8).…”
mentioning
confidence: 99%